PEMANFAATAN ADSORBEN DARI KULIT BUAH KAKAO (Theobroma cacao l.) UNTUK MENURUNKAN CHEMICAL OXYGEN DEMAND PADA PALM OIL MILL EFFLUENT - Setiaty Pandia; Astri Devi Yunita Siahaan; Anita Tiurmaida Hutagalung (Jurnal Teknik Kimia USU, 2017)
This study was aimed to determine the effectiveness of cocoa peel as adsorbents to reduce the content of COD in POME (Palm Oil Mill Effluent). The study was initiated by modifying the adsorbent, where the cleansed and crushed cocoa peels with a size variation of 70-100 mesh, 100-120 mesh, dan ≥120 mesh were activated with 0.6 M HNO3 solution at 1:2, 1:4, and 1:6 of adsorbent : HNO3 ratio while heated at 80 ᵒC for 2 hours. The adsorption process was carried out using variation of adsorbent mass of 1 g, 1,5 g, and 2 g in 50 mL of Palm Oil Mill Effluent at pH 2 and 200 rpm stirring rate, and variation of contact time of 1, 2, 3, 4 , and 5 hours. The study results showed that particle size ≥120 mesh with adsorbent : HNO3 ratio 1:4 produced the highest iodine number of 596,684 mg/g. The best adsorbent mass was 1 g at 2 hours contact time with 56.79% removal percentage for COD. The appropriate kinetics model of the adsorption of COD was the pseudo-second order model with the correlation coefficient of 0.732.